DOP82 Achievement of steroid-free remission in patients with moderately to severely active Crohn's Disease during treatment with risankizumab. (21st January 2022) - Schreiber, S W; Cross, R; Panaccione, R; D'Haens, G; Bossuyt, P; Colombel, J F; Louis, E; Dubinsky, M; Kligys, K; Neimark, E; Song, A; Zambrano, J; et al.
Abstract: Background: The efficacy and safety of risankizumab (RZB) as induction and maintenance therapy for patients with moderately to severely active Crohn's disease (CD) has been documented. Steroid-free clinical remission is an important additional treatment goal in CD. The efficacy of RZB by baseline steroid use during induction and steroid-free outcomes during maintenance was examined. Methods: In ADVANCE (NCT03105128) and MOTIVATE (NCT03104413), patients with moderately to severely active CD received intravenous (IV) RZB induction therapy or placebo (PBO) for 12 weeks. Patients with clinical response to RZB were re-randomised in a 52-week maintenance study (FORTIFY; NCT03105102) to subcutaneous (SC) RZB or PBO (ie, withdrawal). Patients receiving steroids (maximum prednisone or equivalent ≤ 20 mg/day; budesonide ≤ 9 mg/day) at baseline of the induction studies maintained stable doses for the 12-week study duration. A mandatory steroid taper per protocol was initiated at the beginning of maintenance for patients receiving steroids during induction. Patients losing clinical response (per investigator assessment) after initiation of taper could have their steroid dose increased up to the induction baseline dose. This analysis included patients who received RZB 600 mg IV in ADVANCE or MOTIVATE and patients who received RZB 360 mg SC in FORTIFY. Endpoints reported included clinical remission (defined by CD Activity Index [CDAI] or stool frequency/abdominal pain score [SF/APS] criteria) at week 12 of induction by baseline steroid use, steroid-free clinical remission (CDAI or SF/APS), steroid-free endoscopic response, and steroid-free endoscopic remission at week 52 of maintenance. Steroid discontinuation rates over 52 weeks of maintenance were also assessed. Results: Induction of clinical remission at week 12 with RZB 600 mg IV in ADVANCE or MOTIVATE was independent from baseline steroid use (Figure 1 ).Clinical remission rates (CDAI or SF/APS) at week 12 were similar for patients using steroids vs those who were not (33.8%–42.0% vs 34.9%–46.6%; Figure 1 ). Steroid use decreased over time in FORTIFY, with a greater proportion of patients receiving RZB 360 mg SC discontinuing steroids at week 52 vs withdrawal (PBO SC; Figure 2A ). Rates of steroid-free clinical remission ( P ≤ .012), steroid-free endoscopic response ( P < .001), and steroid-free endoscopic remission ( P < .001) were significantly higher with RZB 360 mg SC vs withdrawal (PBO SC) at week 52 of maintenance (Figure 2B–2C ). Conclusion: Efficacy of RZB induction therapy was independent of baseline steroid use. RZB maintenance promotes high rates of steroid-free clinical and endoscopic outcomes, demonstrating a benefit of RZB treatment in CD.